Emergency Nurses’ Perceptions of Obstacles and Supportive Behaviors in Providing End-Of-Life Care - Ariyanti, Santi; Emaliyawati, Etika; Mirwanti, Ristina (Journal of Nursing Care, 2019)
The high mortality rate in Emergency Department (ED) is consistent with the high demand for end of life (EOL) care. However, ED work system required to life saving quickly and precisely often makes EOL care is not working optimally.The purpose of this study was to determine nurses’perceptions in emergency departments related to obstacles and supportive behaviors (SB) in providing EOL care to dying patients. Descriptive-quantitative method was used with cross-sectional approach in 50 nurses Emergency Department at one of the tertiary hospitals in Indonesia. The samples were chosen using the total sampling technique. Data collection used the emergency nurse perceptions of end of life care questionnaire. Data were analyzed using univariate analysis in the form of distribution, frequency, and mean. The result of the study showed that the main obstacles in EOL care were:  ED nurses’ work loads (10.626), intra-family disagreements (9,802), and dealing with angry family members (9.472). The three main perceptions in supportive behaviors were teaching families how to act (11.962), allowing family members adequate time with the patient after patient died (11.09), and good collaboration from paramedics personnel (10.886. It can be conclude that nurses facing obstacles in taking care end-of-life patients. Based on this research, further studies are needed to minimize obstacles and improve supportive behaviors related to the nurse's workload, the provision of spiritual teams, special training for nurse and the provision of special rooms for EOL patients and their families.